Influência da temperatura na ação do fungo Duddingtonia flagrans utilizado como controle biológico de Haemonchus contortus em ovinos - Buske, Rodrigo (2010)
In recent years has increased the search for alternative methods to combat gastrointestinal parasites, and in this context, biological control achieved by the fungus Duddingtonia flagrans draws attention. In this study, we analyze the possibility of the temperature have influence on the nematophagic activity of D. flagrans against the parasites Haemonchus contortus of sheep. We used four sheep, two parasitized with H. contortus and two dewormed. One dewormed sheep received, for three consecutive days before collection of feces, 1 x 106 chlamydospores of D. flagrans, lyophilized, in gelatin capsules. After feces collection, with the aid of collectors bags, they were mixed, resulting in samples with (fungus) and without fungus (control). Each sample was incubated at seven different temperatures (5, 10, 15, 20, 25, 30 and 35 º C) for 21 days. After the incubation period recovery and counting of larvae was performed. The best temperature for fungus action was 30 º C. No larvae were recovered at 5 ºC. From 10 ºC, the fungus action was detected, but there was no significant difference in the percentage of larval reduction between the temperatures, demonstrating that the presence of larvae seems to be the main factor affecting its nematophagic action. It can be concluded that the temperature does not seem to be a limiting factor in the action of Duddingtonia flagrans used for biological control of Haemonchus contortus. Even at lower temperatures, the lyophilized D. flagrans reduced the number of H. contortus larvae, showing, once again, the potentiality of this species in biological control, even in non-ideal conditions for their development and the larvae development, so that it can be used in colder climates, as in Rio Grande do Sul state.